THE IMPACT OF INCREASING ENROLLMENT ON FACULTY WORKLOAD AND STUDENT SATISFACTION OVER TIME - DiBiase, David (Online Learning, 2004)
Detailed daily records of instructor effort in an established asynchronous online course over a three and one-half year period are analyzed. Student satisfaction data acquired from course evaluation surveys over the same period are also examined. In response to a three-fold increase in enrollment over the period, instructors realized a twelve percent gain in efficiency. Contrary to expectations, a modest economy of scale was achieved with no discernible decrease in student satisfaction.